Porno? Chic!: how pornography changed the world and made it a better place - McNair, Brian (Routledge, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals. Brian McNair addresses this relationship with an analysis of trends in sexualised culture since 2002 linked to a transnational analysis of change in sexual politics and sex/gender relations in a range of societies, from the sexually liberalised societies of advanced capitalism to those in which women and homosexuals remain tightly controlled by authoritarian, patriarchal regimes. In this accessible, jargon-free book, Brian McNair examines why those societies in which sexualised culture is the most liberalised and pervasive are also those in which the socio-economic and political rights of women and homosexuals have advanced the most.
Section: xii, 188 p. : ill. ; 24 cm
Keywords: LGBTQIA2+; approches et analyses; communication; cours; discipline; droits des femmes*; féminisme pop; identités LGBTQIA2+; justice sociale; premier cycle; queer; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; études culturelles

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Les éditions du remue-ménage, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Section: 214 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences